Carbon nanodots as dual role of crosslinking and reinforcing chloroprene rubber. (December 2020) - Kong, Lingmin; Zhu, Yong; Huang, Guangsu; Wu, Jinrong
Abstract: The environmental-friendly and sustainable development is a top concern of rubber industry. Here we report a green method to fabricate a class of mechanically robust chloroprene rubber (CR) by employing nitrogen doped carbon nanodots (N-CDs) as both crosslinker and reinforcing nanofillers. The N-CDs are prepared by a green bulk high-temperature carbonization method on large-scale and can crosslink CR by nucleophilic substitution. The vulcanization kinetics are studied by curemeter. Moreover, the covalent crosslinks result in strong interfacial interaction between N-CDs and CR, enabling exceptional reinforcement of the rubber matrix. Consequently, N-CDs crosslinked CR manifests excellent mechanical properties with a tensile stress up to 30 MPa and an elongation at break up to 1353%. With no carcinogenic and environmentally toxic additives included, this work provides a new strategy to prepare high-performance green rubber composites without pollution. Highlights: Green vulcanization of chloroprene rubber (CR) without ZnO and ethylene thiourea. Carbon nanodots simultaneously crosslink and reinforce CR. Nitrogen doped carbon nanodots were prepared without any solvent. A class of mechanically robust composites were fabricated.